The right to life and its coexistence with constitutional rights: Perspective of the constitutional court - Huertas Díaz, Omar (DIXI, 2023)
This article addresses the content of the right to life established by the Colombian Constitutional Court, as a fundamental element for the existence of human beings. Within the framework of the above, the interrelationships and jurisprudential advances that are created with other constitutional rights such as the right to freedom, work, health, vital minimum, environment, among others, are described, which is reflected in the analysis and weighting of particular cases. The article is formulated from a qualitative research, with the implementation of a descriptive method.